Development and Psychometric Validation of a Concussion Symptom Assessment Tool for Combat Sports Athletes - Aedo-Munoz, E; Brito, C (ELSEVIER, 2025)
Objectives To develop and psychometrically validate the Combat Physical and Motivational Symptoms Scale (COMBAT-PMS) for concussion assessment in combat sports athletes. Design Mixed-methods (qualitative-quantitative) design with three sequential stages: theoretical (item generation), empirical (data collection), and analytical (psychometric evaluation). Setting Combat sports community. Participants 409 combat sports athletes: Stage 1 (qualitative/theoretical) involved expert judges; Stage 2 included 204 athletes for exploratory factor analysis (EFA); Stage 3 included 205 athletes for confirmatory factor analysis (CFA). Main outcome measures Validity (expert review, EFA, CFA) and reliability (Cronbach s alpha). Results EFA reduced items from 38 to 23 (KMO = 0.848; Bartlett s p < 0.001), revealing two correlated factors: Physical Symptoms (11 items) and Motivational Symptoms (12 items), explaining 54.8 % variance. CFA confirmed the model (DWLS estimation), showing excellent fit. High internal consistency was found (Physical alpha = 0.87; Motivational alpha = 0.96), with significant factor correlation (r = 0.54, p < 0.001). The bifactor structure was validated as psychometrically robust. Conclusion The COMBAT-PMS is a reliable, valid 23-item scale integrating physical and motivational concussion symptoms. It pioneers targeted assessment for combat sports, enabling early detection of head trauma impacts and challenging pain normalization to support safer athletic careers.